Xinfeng capsule improves hyperinflammation-associated hypercoagulability and self-perception in osteoarthritis by regulating KLF4 through METTL14-mediated m6A modification of lncRNA MEG3 - He, Mingyu; Liu, Jian; Sun, Yanqiu; Fang, Yanyan; Wang, Fanfan (Frontiers in Immunology, 2026)
BackgroundOur previous studies have demonstrated that Xinfeng Capsule (XFC) exerts therapeutic effects on hyperinflammation-associated hypercoagulability and self-perception of patients (SPP) with osteoarthritis (OA). However, the underlying molecular mechanisms remain unclear.ObjectiveThis study aimed to explore the mechanism by which XFC improves hyperinflammation-associated hypercoagulability and SPP in OA.MethodsA keyword co-occurrence network was constructed to identify key targets involved in hyperinflammation-associated hypercoagulability in OA patients. m6A prediction databases and RNA pull-down assays were used to identify potential m6A modification sites and key binding proteins of lncRNA MEG3. Peripheral blood mononuclear cells (PBMCs) were collected from OA patients and healthy controls, and global m6A levels were measured using a colorimetric assay. Methylated RNA immunoprecipitation quantitative polymerase chain reaction (MeRIP-qPCR) was used to detect m6A modification levels of lncRNA MEG3. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) and Western blot (WB) were performed to determine the mRNA and protein expression levels of target genes. Enzyme-linked immunosorbent assay (ELISA) was used to measure inflammatory and coagulation-related factors. Finally, clinical data mining was conducted to clarify the clinical efficacy of XFC in improving hyperinflammation-associated hypercoagulability and SPP in OA patients, and in vitro experiments were performed to validate the underlying mechanisms.ResultsThe keyword co-occurrence network analysis indicated that inflammatory factors [interleukin-6 (IL-6), IL-10, and tumor necrosis factor-α (TNF-α)] and coagulation-related factors [tissue factor (TF), plasminogen activator inhibitor-1 (PAI-1), and prostaglandin I2 (PGI2)] are involved in the regulation of hyperinflammation-associated hypercoagulability in OA patients. PBMC analysis further confirmed these findings. In addition, the expression levels of lncRNA MEG3 and its target gene KLF4 were significantly decreased in OA patients and were closely associated with clinical indicators of inflammation, coagulation, and SPP. Methyltransferase-like 14 (METTL14) expression was significantly increased in OA patients and was negatively correlated with lncRNA MEG3 expression. Clinical data mining revealed that XFC is a key therapeutic agent for improving hyperinflammation-associated hypercoagulability and SPP in OA patients. XFC treatment reduced the expression levels of METTL14, pro-inflammatory factors, and procoagulant factors, while increasing the levels of lncRNA MEG3, KLF4, anti-inflammatory factors, and anticoagulant factors. In vitro These findings were further validated by in vitro experiments.ConclusionThis study indicates that XFC may upregulate the expression of lncRNA MEG3 and KLF4 by modulating METTL14-mediated m6A modification of lncRNA MEG3. Through this mechanism, XFC may regulate inflammatory responses and coagulation disorders, thereby improving SPP and exerting therapeutic effects on hyperinflammation-associated hypercoagulability in patients with OA.